The best of me [videorecording (DVD)] - Hoffman, Michael, 1956-; Monaghan, Michelle; Marsden, James, 1973-; Bracey, Luke, 1989-; McRaney, Gerald; Tenney, Jon, 1961-; Sparks, Nicholas (Twentieth Century Fox Film Entertainment, 2014)
The story of Dawson and Amanda, two former high school sweethearts who find themselves reunited after twenty years apart, when they return to their small town for the funeral of a beloved friend. Their bittersweet reunion reignites the love they've never forgotten, but soon they discover the forces that drove them apart twenty years ago live on, posing even more serious threats today.